Projected Freshwater Withdrawals Under Efficiency Scenarios for Electricity Generation and Municipal Use in the United States for 20301. (10th December 2012) - Chen, Limin; Roy, Sujoy B.; Goldstein, Robert A.
<x xml:space="preserve">Abstract</x> Chen, Limin, Sujoy B. Roy, and Robert A. Goldstein, 2012. Projected Freshwater Withdrawals Under Efficiency Scenarios for Electricity Generation and Municipal Use in the United States for 2030. Journal of the American Water Resources Association (JAWRA) 1‐16. DOI: 10.1111/jawr.12013 Abstract: Water withdrawals in the United States (U.S.) have been relatively uniform over the past two decades on a nationally aggregated basis, although on a more highly resolved geographical basis, increases have occurred, largely associated with growth in population and the cooling needs for new electricity generation. Using recent county‐level water use data, we develop projections for five different scenarios, bracketing a range of future conditions, and representing different levels of efficiency in the municipal and electricity generation sectors, where the municipal sector includes public and self‐supplied domestic withdrawals. Starting with the 2005 estimate of 347 billion gallons per day (bgd) of freshwater withdrawal in the continental U.S., our analysis shows that under a business‐as‐usual scenario of growth, there will be a need for additional water over current levels: 11 bgd in the municipal sector, with a smaller requirement for new electricity generation (1 bgd). However, we also estimate that withdrawals could be reduced significantly over current levels, through increased water use efficiencies in the electric power and municipal sectors. The study shows that if water withdrawals are to be held at their current levels for the thermoelectric and municipal sectors individually at a county level over the next 25 years, large improvements in efficiency will be needed in many parts of the Southeast and Southwest.